Green Military New Deal - Eduardo Castillo-Vinuesa; Iuliia Gankevich (Temes de Disseny)
Among the most decisive challenges that the climate crisis will bring during up coming decades will be the necessity to overcome the current lack of planetary ecosystem governance. The void that exists where proper geopolitics should reside demands a recalibration of the focus of design towards the conception, implementation, and support of new institutional models capable of reconfiguring established infrastructural, ecosystem and governance structures.